QoE-driven centralized scheduling for HTTP adaptive video streaming transmission over wireless networks - Tiantian Li; Haixia Zhang; Jie Tian; Shuaishuai Guo (International Conference on Wireless Communications and Signal Processing, 2017)
In this paper, we propose a novel QoE-driven centralized scheduling framework to satisfy the differentiated quality of experience (QoE) requirements of cellular users for HTTP-based video streaming transmission. The framework jointly considers the comprehensive information from the video server side (video coding rates and QoE parameters), the user side (video playback buffer occupancy), and the time-varying wireless channel side (channel state information-CSI). A mixed binary integer programming problem is formulated to maximize the overall user QoE through the effective weighted resource allocation and video coding rate adaptation, which is implemented by the centralized scheduler residing at the Base Station (BS). Our heuristic algorithm can be considered as a proactive one that enables the proxy at the BS to rewrite the HTTP requests. In particular, the impact of delay factor on the performance of average rebuffering time is analyzed. Simulation results demonstrate that our proposed scheme performs effectively in enhancing the user QoE satisfaction and outperforms the four benchmarks.